On dividing p(4p² - 16) by 4p(p - 2), we get
(a) 2p + 4
(b) 2p - 4
(c) p + 2
(d) p - 2
Solution:
Correct option is (c ).
Given, divide p(4p² - 16) by 4p (p - 2)
= p (4p² - 16) / 4p (p - 2)
= p 4(p² - 4) / 4p (p - 2)
Here, (4p² - 16) is in the form of the standard identity a² - b² = (a + b) (a - b).
∴ p 4(p² - 4) / 4p (p - 2)
= p 4[(p)² - (2)²] / 4p (p - 2)
= p 4(p + 2)(p - 2) / 4p (p - 2)
Canceling the common terms,
= (p + 2)
✦ Try This: On dividing x(16x² - 64) by 2x(x - 2) is (a) 8(x + 2), (b) (x + 2), (c) 8(x - 2), (d) (x - 2)
Correct option is (a)
Given, divide x(16x² - 64) by 2x(x - 2)
= x(16x² - 64)/ 2x(x - 2)
= 16x(x² - 4) / 2x(x - 2)
= 16x(x + 2)(x - 2)/2x(x - 2)
= 8(x + 2)
☛ Also Check: NCERT Solutions for Class 8 Maths Chapter 9
NCERT Exemplar Class 8 Maths Chapter 7 Problem 23
On dividing p (4p² - 16) by 4p (p - 2), we get (a) 2p + 4, (b) 2p - 4, (c) p + 2, (d) p - 2
Summary:
On dividing p (4p² - 16) by 4p (p - 2), we get p + 2
☛ Related Questions:
visual curriculum